Low frequency of recent parvovirus infection in a population-based cohort of patients with early inflammatory polyarthritis - Harrison, B. (1998)
OBJECTIVE—To determine the contribution of human parvovirus B19 infection in explaining the incidence of early inflammatory polyarthritis (IP) in a population. SETTING—The Norfolk Arthritis Register (NOAR) is a community-based programme aiming to ascertain all new cases of IP arising in a population that lead to attendance at primary care. SUBJECTS—147 newly ascertained subjects with IP with a disease duration of less than 16( )weeks. METHODS—Full clinical appraisal of all subjects who were followed up for three years. B19 IgM assayed with a third generation antibody capture enzyme immunoassay. RESULTS—Only four (2.7%) patients had evidence of recent B19 infection, only one of whom did not satisfy criteria for rheumatoid arthritis (RA). CONCLUSION—B19 infection does not explain more than a small proportion of either RA or undifferentiated IP cases occurring in the population.   Keywords: rheumatoid arthritis; epidemiology; human parvovirus B19